Empowering settings and voices for social change - Aber, Mark S. (Mark Stephen), 1958-; Maton, Kenneth I.; Seidman, Edward (New York ; Oxford : Oxford University Press, 2011)
This edited volume combines a focus on understanding social settings as loci for empowering intervention with a focus on understanding and giving voice to citizens. It illuminates advances in theory and method relevant to changing a broad spectrum of social settings from a strengths-based perspective.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Social change; Social psychology; Power (Social sciences)